European Union Strategies Extrapolation for Boosting Students’ Media Literacy in Ukrainian Higher Education - Bilotserkovets, Marina; Fomenko, Tatiana; Lushchyk, Yuliia (Educational Challenges, 2023)
Purpose. The paper deals with the realization of Erasmus+ Jean Monnet Module project that contributes to the strengthening of the role of media literacy among citizens. The aim of the article is to regard practical aspects of media literacy and critical thinking development for higher education (HE) institution’ students in the context of foreign language learning, considering European and Ukrainian experiences. Methodology of the study involved analysing and generalizing scientific sources to uncover the main issues under investigation; collecting and summarizing valuable points from scholars’ contributions worldwide, intercultural communication observations and descriptions. Results. The project “European Union (EU) strategies extrapolation for boosting students’ media literacy in Ukrainian HE”, initiated in SNAU with the support of Jean Monnet Foundation within the EU Erasmus+ Program, is targeted at popularizing the main directions of EU policy in the field of media education. While reviewing the European discourse on media literacy it was found that the key strategies in British media education are media authorship, ownership and control, ways of achieving the effect of influence and encoding information of media texts, etc. Finnish media education’s overall goal is enabling students’ analysis of the present and the desired future, and decision making to move towards the desired future. Media education in France is largely determined by semiology, discourse analysis, film analysis, promoting citizens’ participation in the public life, a critical approach to advertising and active resistance to its influence. Austrian and German media education focuses on the control over media with potentially harmful or dangerous content and the development of responsible communication culture. Integrating media literacy into foreign language training is revealed to be essential as it can introduce real-world topics and scenarios relevant to students. The compilers of the training course syllabus considered important European documents on media literacy and language education selecting topics, establishing learning objectives, defining learning outcomes, and setting evaluation criteria. Conclusions: The results of this study suggest that media literacy skills should be a compulsory subject in all branches of educational faculties and developed throughout life. The training course should be based on advanced innovations and achievements in this field, considering European and Ukrainian experiences.